The effect of innovation on the financial performance and export intensity of firms in emerging countries - Quelhas, Filipe de Castro (Revista de Administração da UFSM, 2021)
Purpose – What impact does innovation have on the financial performance and export intensity of firms in emerging countries? Design/methodology/approach – This contribution is the result of an analysis of five years’ data (2008-2012) from a multinational survey conducted with 140 predominantly manufacturing firms from Brazil, Russia, India, China. Findings – In contrast with the prevailing literature, the results reveal strong positive correlations between the principal study variables. Originality/value – Studies of this subject have found contradictory results with regard to the effect of innovation on firm performance. Only a minority of these studies have operationalized their investigations using historical data from a range of different countries and fewer still have focused on emerging countries.This article contributes to the debate by reporting the effects of innovation activity by firms from emerging countries on their financial performance and export intensity.